Security and Historical Politics: Analysis of the Operations of the Russian Federation in the 21st Century - Polak, Michał; Kaczmarek, Krzysztof (Roczniki Nauk Społecznych, 2025)
The manipulation of history is one of the elements of hybrid activities conducted by the Russian Federation, especially in the context of the aggressive international policy pursued by this country. Using methods of discourse analysis, case studies, and comparative analysis, the authors show how manipulation of historical facts can lead to destabilisation of international security, polarisation of societies and strengthening of Russia’s political influence. The securitisation of historical policy and the growing role of social media in the propagation of distorted narratives are also discussed. The research results indicate that effective counteracting historical disinformation requires both historical education and developed information protection mechanisms.